Implikasi Hukum Putusan Mahkamah Konstitusi Nomor : 23/PUU-XIX/2021 Bagi Pengurus dan Kreditor - Mahrus Mahrus; Yahman Yahman (Pusat Riset dan Inovasi Nasional, 2024)
Postponement of Debt Payment Obligations (PKPU) is a legal mechanism that provides a grace period for creditors and debtors to negotiate debt settlement through the courts. Based on Law Number 37 of 2004, previously no legal action was permitted against PKPU decisions. However, the issuance of Constitutional Court Decision Number 23/PUU-XIX/2021 changed this provision by allowing the submission of an appeal against a PKPU decision submitted by a creditor if the debtor's peace proposal is rejected. This study aims to examine the philosophy and legal and practical implications of the decision for PKPU administrators and creditors. The research method used is normative with a statutory, conceptual, and document study approach. The results of the study show that the Constitutional Court decision creates legal uncertainty, an imbalance of responsibility, and prolongs the PKPU settlement process. This disrupts the principle of a speedy trial and has the potential to create a legal vacuum regarding the authority of administrators in carrying out their duties during the cassation process. Thus, this legal change requires special attention in its implementation to maintain balance and legal certainty for the parties concerned.